Observational study of adult respiratory infections in primary care clinics in Myanmar: understanding the burden of melioidosis, tuberculosis and other infections not covered by empirical treatment regimes - Warrell, CE; Phyo, AP; Win, MM; McLean, ARD; Watthanaworawit, W; Swe, MMM; Soe, K; Lin, HN; Aung, YY; Ko, CK; Waing, CZ; Linn, KS; et al. (Oxford University Press, 2021)
Background Lower respiratory infections constitute a major disease burden worldwide. Treatment is usually empiric and targeted towards typical bacterial pathogens. Understanding the prevalence of pathogens not covered by empirical treatment is important to improve diagnostic and treatment algorithms.